2022
DOI: 10.1186/s40168-022-01322-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal disease-associated gut microbiome differences in infants with food protein-induced allergic proctocolitis

Abstract: Background Complex interactions between the gut microbiome and immune cells in infancy are thought to be part of the pathogenesis for the marked rise in pediatric allergic diseases, particularly food allergies. Food protein-induced allergic proctocolitis (FPIAP) is commonly the earliest recognized non-immunoglobulin E (IgE)-mediated food allergy in infancy and is associated with atopic dermatitis and subsequent IgE-mediated food allergy later in childhood. Yet, a large prospective longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Furthermore, a subsequent study, using a subset of GMAP participants during the 0-2 months period, identi ed distinct microbial differences. Speci cally, the study revealed higher levels of an unidenti ed genus within Enterobacteriaceae and lower levels of an unidenti ed family within Clostridiaceae in FPIAP cases compared to controls [22]. In our study there were no difference in relative abundance of Clostridiaceae and Enterobactericeae between the two groups.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, a subsequent study, using a subset of GMAP participants during the 0-2 months period, identi ed distinct microbial differences. Speci cally, the study revealed higher levels of an unidenti ed genus within Enterobacteriaceae and lower levels of an unidenti ed family within Clostridiaceae in FPIAP cases compared to controls [22]. In our study there were no difference in relative abundance of Clostridiaceae and Enterobactericeae between the two groups.…”
Section: Discussionsupporting
confidence: 48%
“…51 Gut microbiota has a crucial role in the development of allergic diseases such as intestinal inflammatory diseases, asthma, and AD. [52][53][54] Metabolites produced by the gut microbiota, such as amino acid metabolites, short chain fatty acids (SCFAs), and oligosaccharides, can form a mucosal layer and constitute the intestinal barrier to prevent microorganisms from entering the bloodstream and causing infection. 55 There are numerous factors that affect the immune equilibrium between the gut microbiota and the host, including diet, disease, and others.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…There is a mounting body of evidence that the gut microbiota is impacted directly by diet, inflammation, and environment, and the microbiota subsequently impacts disease state ( 12 ). Recent data from the Gastrointestinal Microbiome and Allergic Proctocolitis study demonstrated key differences in the microbiome of infants with FPIAP, specifically a higher abundance of a genus of Enterobacteriaceae and a lower abundance of a family of Clostridiales during the symptomatic period, with some differences noted prior to symptom onset ( 13 ). The authors concluded that complex cross talk between the intestinal microbiome, food antigens, intestinal inflammation, and the innate immune system early in life likely contributes to the mechanisms responsible for either healthy tolerance or food allergy development ( 13 ).…”
Section: Introductionmentioning
confidence: 99%